PICTO-TEXT GLOSSES TO ENHANCE STUDENTS’ READING COMPREHENSION - Luki Emiliya Hidayat (IAIN MADURA, 2016)
One of students’ difficulties in comprehending a reading text is their limited vocabulary. Therefore, this article is aimed to provide practical recommendation for EFL teachers to use picto-text (pictorial and textual) glosses in reading materials to help students’ become familiar to the terms used in the text that will eventually improve their reading comprehension.